How to choose between the implant materials steel and titanium in orthopedic trauma surgery. Part 1, Mechanical aspects - Perren, S. M; Regazzoni, P; Fernandez, A. A (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2017)
When choosing between metal implants of different materials the surgeon mainly needs to balance the pros and cons of steel and titanium. Economic constraints often do not permit both to be kept in stock and it is necessary to decide beforehand which to choose. The arguments for the use of the "preferred metal" vary. The present paper elucidates the practical aspects based on the complex scientific background that has identified the differences between the two metals in their mechanical, electrochemical, biological and application behavior. The data presented here are intended to help the surgeon when he is confronted with different and often complex clinical situations and problems. The following is an overview of different aspects to help with selection of the proper material for the clinical application. The first part concerns mechanical aspects the second part the biological aspects. Both aspects are discussed with the practical application in mind. Nonmetallic implant materials have seen an increasing interest in the recent past. Plastic materials needed improvement to achieve good strength and avoid creep with loss of e.g. compression and minimizing leakage of chemicals.
Keywords: testování materiálů; ortopedické výkony; titan; biomechanika; lidé; protézy a implantáty; ocel; Materials Testing; Titanium; Orthopedic Procedures; Steel; Prostheses and Implants; Biomechanical Phenomena; Humans